Legal Protection of Copyright in Digital Content on Social Media under Law Number 28 of 2014 concerning Copyright - Rafli Ramdani; Rihan Rizky; Fathir Putra Maulud; Ikhwan Aulia Fatahillah (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study analyzes the legal protection of digital content copyright on social media under Law Number 28 of 2014 concerning Copyright. The rapid expansion of social media platforms has accelerated the creation, dissemination, and commercialization of digital content, including videos, photographs, music, graphic designs, and live-streaming content, while simultaneously increasing the prevalence of copyright infringement. Common violations include unauthorized re-uploading, removal of attribution, unauthorized modification, and commercial exploitation without the consent of copyright holders. This normative legal research employs statutory, conceptual, and analytical approaches using primary legal materials, including Law Number 28 of 2014, as well as secondary materials derived from legal doctrines and scholarly publications. The findings indicate that the Copyright Law provides comprehensive protection through the declarative principle, moral rights, economic rights, technological protection measures, rights management information, and notice-and-takedown mechanisms within electronic systems. The study also finds that copyright enforcement is supported through administrative, civil, and criminal remedies designed to address various forms of infringement. Despite the adequacy of the normative framework, enforcement remains constrained by challenges related to digital evidence, cross-border jurisdiction, technological developments, and limited public awareness. The study concludes that strengthening institutional coordination, digital copyright literacy, and platform cooperation is essential for improving the effectiveness of copyright protection in social media environments.